ADMINISTRATIVE JURIDICAL STUDY OF THE POSITION OF MALAY TRADITIONAL INSTITUTIONS IN BANGKA REGENCY (A FORM OF PRESERVING THE NOBLE VALUES OF MALAY TRADITIONAL AND CULTURAL VALUES) - Wirazilmustaan; Robuwan, Rahmat (Bengkoelen Justice : Jurnal Ilmu Hukum, 2023)
The Malay Traditional Institute of Bangka Regency, which was founded in 2014, is an institution that is based on Islam and espouses Pancasila and the 1945 Constitution. Research analysis, the method used as an approach in this research is juridical-empirical, using research specifications are descriptive. The Malay Traditional Institute of Bangka district is an institution that aims to explore, foster, maintain and develop the noble values of Malay customs in Bangka district as a foundation and strengthen Malay identity. Bangka Regency, as one of the regencies in the Bangka Belitung Islands Province, in principle has various noble values and very diverse customs and culture. Therefore, through Bangka Regent Regulation Number 4 of 2017 concerning the Preservation and Development of Community Customs and Socio-Cultural Values, several customs in Bangka Regency are stipulated. The results of this research show that LAM Bangka does not yet have a strong legal and administrative position because there are no implementing regulations from the Regional Regulation of the Bangka Belitung Islands Province Number 4 of 2012 concerning the Preservation of Customs and Empowerment of Malay Traditional Institutions in the Bangka Belitung Islands. Even though it only regulates culture or customs without regulating institutions in preserving Malay traditional and cultural values. suggestions that can be conveyed are to carry out an inventory of manuscripts, oral traditions, customs, rites, traditional knowledge, traditional technology, language, folk games and traditional sports spread across Bangka Regency. Keywords: Administrative Jurisdiction, Malay Traditional Institutions, Conservation